Interaction of bacteriophage K10 with its receptor, the lamB protein of Escherichia coli. - Roa, M (1979)
The lamB protein of Escherichia coli was initially recognized as the receptor for bacteriophage lambda. It is now shown also to constitute the receptor for phage K10. The lamB protein interacts with phage K10 in vitro, but this interaction does not lead to phage inactivation. Most lambda-resistant labB mutants are also resistant to K10, and vice versa. However, a significant proportion of the mutants resistant to one of the phages is sensitive to the other. Nineteen K10-resistant lambda-sensitive mutants have been studied. Only six of them produce a lamB protein which seems totally unimpaired in its ihe same deletion interval of the lamB gene. The corresponding region of the lamB polypeptide must be specifically involved in the interaction with phage K10. An unusual pattern of K10 host range mutants has been obtained; two calsses of such mutants could be defined, growing on two distinct classes of K10-resistant lamB mutants.